Enhancing Usage Behavior of E-Procurement Through Organizational Values - Hery Suliantoro; Kirana Rukmayuninda Ririh (Jurnal Ilmiah Teknik Industri, 2019)
The main purpose of this paper is to examine empirically the influence of organizational factors on the adoption of e-procurement in government institutions.The research design used is a survey research. This study examines theoretical models involving 185 respondents from 130 work units of all local government agencies in Central Java, Indonesia. Data analysis was done by using structural equation to know influence of organization value in e-procurement adoption process in government institution. The result of the research shows that organizational polychronicity values influence the behavior of e-procurement. Characteristics of dynamic organizational functions and tasks directly enhance the use of e-procurement behavior. Another finding, the learning organization has an effect on the e-procurement intention. The ability or capacity of the organization provides an opportunity for individuals to do individual learning will further activate the process of adoption of various applications of e-procurement. An important result of this study is that organizational value is one of the main determinants of successful adoption of technology. The findings of this study provide insight into the importance of organizational value in supporting the successful implementation of e-procurement.